IMPROVING PEDAGOGIC PROFESSIONALISM TEACHING TK, SD, SMP/MTS TEACHERS TRAINING THE MOTIVATOR STYLE (MGM) AS AISYIYAH CIRACAS EAST JAKARTA - Nurmawati, Nurmawati; Fitri Meilana, Septi (Devotion : Journal of Research and Community Service, 2021)
Teaching in principle guides students in teaching and learning activities or implies that teaching is an effort to organize the environment in relation to students and teaching materials that lead to the learning process. Pedagogic competence is the ability of teachers to manage learning, at least covering understanding of educational insights or foundations, student understanding, curriculum/syllabus development, learning design, implementation of educative and dialogical learning, use of learning technology, evaluation of learning processes and outcomes, and development of students to actualize various potentials. This study aims to analyze the improvement of teacher professionalism through motivational style training. This study uses qualitative methods with data collection techniques through observation. The results of this study indicate that the planning stage was carried out well although there were still some shortcomings. LPPM's coordination with the implementation team has been maximized. However, the coordination between the implementation time and partners is still lacking in terms of implementation time which then has implications for the number of participants. Both implementations were quite good, the number of participants had reached the target even though it seemed urgent. In terms of time still not good enough. The third stage of the evaluation is carried out well enough so that it can correct the existing deficiencies.